Assessing the impact of rice-wheat-maize residue decomposition rate and nutrient dynamics of residue and soil using different placement method in the IGP of India - Mishra, Ajay Kumar; Shinjo, Hitoshi; Jat, Hanuman Sahay; Jat, Mangi Lal; Jat, Raj Kumar; Funakawa, Shinya (Frontiers in Sustainable Food Systems, 2024)
The rice-wheat cropping system (RWCS) provides the world’s population with staple foods, and it is crucial to maintain global food demand and security. Food systems are a complex ecosystem and sustain many feedback mechanisms. Crop residue management is one of those feedback mechanisms that was assessed under conservation agriculture, and a decomposition study was analyzed for the rice-wheat cropping system using rice, wheat, and maize crop residue for decomposition rate and nutrients release under agricultural practices (zero till, raised beds). Different zero tillage techniques in Samastipur demonstrated an accelerated decomposition trend, which was especially noticeable in the straw from wheat and rice. At the same time, permanent bed systems showed a relatively larger residue mass, especially in the case of wheat and maize straw. Permanent bed systems (wheat-maize system), particularly those using wheat straw, held the largest amounts of residue mass when the total residue mass throughout the sites was taken into account. Samastipur showed higher nutrient release for all the rice residue in wheat, rice residue in maize, and wheat residue in rice except maize residue in rice as compared to the Karnal sites. Decomposition kinetics, modeled via a first-order exponential decay function, showed high correlations (R2: 0.941 to 0.996) across treatment methods. The research underscores the significant effect of agroecological factors on residue decomposition and nutrient release, irrespective of residue type, highlighting the importance of tailored residue management practices for enhanced nutrient cycling and sustainability. These findings contribute to the optimization of residue management strategies in RWCS, promoting sustainable agriculture practices in the face of climate change and increasing food security demands.